From 'foreign natives' to 'native foreigners : explaining xenophobia in post-apartheid South Africa : citizenship and nationalism, identity and politics - neocosmos, michael (Codesria book series., 2010)
"The events of May 2008 in which 62 people were killed simply for being 'foreign' and thousands were turned overnight into refugees shook the South African nation. This book is the first to attempt a comprehensive and rigorous explanation for those horrific events. It argues that xenophobia should be understood as a political discourse and practice. As such its historical development as well as the conditions of its existence must be elucidated in terms of the practices and prescriptions which structure the field of politics. In South Africa, the history of xenophobia is intimately connected to the manner in which citizenship has been conceived and fought over during the past fifty years at least ..."-- Back cover.